Pemberdayaan masyarakat melalui pembuatan Selai Jeruk Kuok di Dusun Pulau Belimbing, Desa Kuok, Kec. Kuok, Kab. Kampar - Edo Saputra; Emma Riftyan; Yossie Kharisma Dewi; Anthony Hamzah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Kuok Village is one of the villages in the Kuok sub-district which has an area of ​​6000 hectares. The population in this village is 8352 people. The majority of the population in the Kuok village works as farmers. One of the commodities that cultivated by farmers is the orange orchard. Oranges in this village are still managed in fresh form and have not been made into a by-product. Hence, the Unri Community Service Team diversified its oranges derivative products, namely marmalade. The purpose of this community service is to solve the decay of oranges during the harvest season by processing oranges into marmalade that can increase community income. The methods used are survey, socialization and training. The process of making this jam begins with peeling the oranges, then all that is taken is the oranges flesh then mashed, then boiled the orange juice until it boils, then added sugar and put it in until the temperature is 105ºC, then the jam is placed in a jar.